PENGARUH PENAMBAHAN KAPUR TERHADAP NILAI KOHESIVITAS TANAH DALAM UPAYA MENINGKATKAN DAYA DUKUNG PONDASI DANGKAL - Riva Putri Fadillah; Eko; raisa (Journal of Sustainable Civil Engineering (JOSCE), 2026)
Clay soils with high plasticity generally exhibit low cohesion and bearing capacity, which may reduce the stability and performance of shallow foundations. One of the commonly applied soil improvement methods to enhance the mechanical properties of clay soil is lime stabilization. This study aims to analyze the effect of lime stabilization on the improvement of soil cohesion and the bearing capacity of shallow foundations in clay soil. Soil samples were collected from the Baleendah area, Bandung Regency, and mixed with 6.67% lime, followed by curing periods of 7, 14, and 120 days. Laboratory testing included water content, specific gravity, sieve analysis, hydrometer analysis, Atterberg limits, and Unconsolidated Undrained (UU) triaxial testing to determine the soil shear strength parameters. The obtained cohesion and internal friction angle values were subsequently used in the bearing capacity analysis of square shallow foundations based on Terzaghi’s method. The results indicate that lime addition and longer curing periods significantly improved the mechanical characteristics of the soil. The cohesion value increased from 21.88 kN/m² in the natural soil to 41.29 kN/m² after 120 days of curing, while the internal friction angle increased from 3.88° to 7.68°. These improvements in shear strength parameters directly contributed to the increase in the ultimate bearing capacity from 240.54 kN/m² to 509.32 kN/m². The findings demonstrate that lime stabilization is effective in improving the cohesion and bearing capacity of clay soils and has strong potential as a soil improvement method for shallow foundation construction.